Conical Grate Rice Husk Combustor for Grain Drying - Hien, Phan Hieu; Quick, Graeme R.; Cruz, Ibarra E. (Philippine Engineering Journal, 2021)
An experimental conical grate rice husk furnace was designed, fabricated, and tested in Los Banos at the Agricultural Engineering Division of the International Rice Research Institute. Experiments were performed with the furnace under suction from an axial-flow fan. Drying air efficiency of the furnace was found to lie in the range 60-80%. At a rice husk burning rate of 32-38 kg/hr, the furnace was compatible with a flat-bed dryer demand of 4-6 tons/batch for 6-8 hr continuous operation. The furnace has a simple cable-type transmission which provides synchronized fuel feeding and ash discharge and is lightweight relative to its heat load.  The charred ash from the furnace contained from 6 to 15% unburnt carbon and was amorphous, as examined by the X-ray diffraction method. Problems in continuous operation of the gasifier-combustor were identified, the major constraint being rice husk feeding flow at high temperature. A rice husk gasification equilibrium (RHGE) model was developed to predict gasifier performance. The model used a reactivity factor Rf to account for biomass reactivity relative to that of graphite, and took account of the ash content and the %Unburnt carbon of rice husk in the mass and heat balance equation. Comparison between RHGE model-generated data and published experimental data showed that the model adequately predicted gasifier performance. Key words: Rice husk, Furnace, Combustion, Gasification, Drying, Modeling